The complete chloroplast genome of Lilium rosthornii Diels (Liliopsida: Liliaceae) from Hunan, China - Wu, Hongzhi (Mitochondrial DNA B Resour, 2021)
Lilium rosthornii is the perennial herbaceous bulbous plant belonging to the Lily of the Liliaceae, with high ornamental value and medicinal values. In this present study, we sequenced the complete chloroplast genome of Lilium rosthornii by Illumina Hiseq X Ten and PacBio RS technologies firstly. The genome size of L. rosthornii, was 152,242bp, with typical tetragonal structure: one large single-copy (LSC, 81,875 bp), one small single-copy (SSC, 17,553 bp), and a pair of inverted repeat regions (IRs, 26,407 bp). The overall GC content was 37.02%. The complete genome contained 131 genes, including 85 protein-coding genes, 38 tRNA genes, and eight rRNA genes. Phylogenetic analysis placed L. rosthornii under the family Liliaceae.